Exploration and analysis of R-loop mapping data with RLBase. Issue Volume 51:Issue D1(2023) (30th August 2022) - Miller, Henry E; Montemayor, Daniel; Li, Janet; Levy, Simon A; Pawar, Roshan; Hartono, Stella; Sharma, Kumar; Frost, Bess; Chedin, Frédéric; Bishop, Alexander J R
Abstract: R-loops are three-stranded nucleic acid structures formed from the hybridization of RNA and DNA. In 2012, Ginno et al . introduced the first R-loop mapping method. Since that time, dozens of R-loop mapping studies have been conducted, yielding hundreds of publicly available datasets. Current R-loop databases provide only limited access to these data. Moreover, no web tools for analyzing user-supplied R-loop datasets have yet been described. In our recent work, we reprocessed 810 R-loop mapping samples, building the largest R-loop data resource to date. We also defined R-loop consensus regions and developed a framework for R-loop data analysis. Now, we introduce RLBase, a user-friendly database that provides the capability to (i) explore hundreds of public R-loop mapping datasets, (ii) explore R-loop consensus regions, (iii) analyze user-supplied data and (iv) download standardized and reprocessed datasets. RLBase is directly accessible via the following URL: https://gccri.bishop-lab.uthscsa.edu/shiny/rlbase/ .